Reversible pH Switch of Two‐Quartet G‐Quadruplexes Formed by Human Telomere. (6th January 2016) - Galer, Petra; Wang, Baifan; Šket, Primož; Plavec, Janez
Abstract: A four‐repeat human telomere DNA sequence without the 3′‐end guanine, d[TAGGG(TTAGGG)2 TTAGG] ( htel1‐ΔG23 ) has been found to adopt two distinct two G‐quartet antiparallel basket‐type G‐quadruplexes, TD and KDH + in presence of KCl. NMR, CD, and UV spectroscopy have demonstrated that topology of KDH + form is distinctive with unique protonated T18⋅A20 + ⋅G5 base triple and other capping structural elements that provide novel insight into structural polymorphism and heterogeneity of G‐quadruplexes in general. Specific stacking interactions amongst two G‐quartets flanking base triples and base pairs in TD and KDH + forms are reflected in 10 K higher thermal stability of KDH + . Populations of TD and KDH + forms are controlled by pH. The (de)protonation of A20 is the key for pH driven structural transformation of htel1‐ΔG23 . Reversibility offers possibilities for its utilization as a conformational switch within different compartments of living cell enabling specific ligand and protein interactions.